Unveiling the diverse medicinal properties of Murraya koenigii (Sciences of Phytochemistry, 2023)
Since the beginning of time, nature has provided medicines for treating fatal illnesses. Herbalists believe that certain plants have medicinal qualities. In tribal and rural communities, medicinal plants provide as an easily accessible source of treatment. The identification of various rejuvenating molecules that can halt or lessen the pathology of a variety of diseases will be regarded as a significant development of the present. There has been a scientific advancement in this area, and current studies on herbal medicines and traditional cures have attracted significant interest from all over the world. This plant, popularly known as the curry tree, is frequently used as herb and is also used to treat a variety of problems in traditional Indian medicine. About 80–85% of people worldwide rely on herbal products because they are thought to be efficient, secure, and cost-effective. Reviewing the plant taxonomy, ethnobotanical characteristics, folkloric or traditional uses, phytochemical, and pharmacological qualities of the Murraya koenigii plant was the goal of the current study. The leaves are used internally for dysentery as a carminative, tonic, stomachic, and inducer of vomiting. The usage of other parts includes treating piles, preventing helminthiasis, and reducing body heat, itchiness, and inflammation. Following several reports that this plant may treat a wide range of illnesses, scientists have worked to confirm the effectiveness of this plant by biological screening. A review of the literature suggests that Murraya koenigii has various medical benefits, including activity of antimicrobial, cardiac, anti-oxidative, anti-diabetic and cholesterol reduction, cytotoxic action, antiulcer, and anti-diarrhea.